2020
DOI: 10.3390/s20174809
|View full text |Cite
|
Sign up to set email alerts
|

Portable LiDAR-Based Method for Improvement of Grass Height Measurement Accuracy: Comparison with SfM Methods

Abstract: Plant height is a key indicator of grass growth. However, its accurate measurement at high spatial density with a conventional ruler is time-consuming and costly. We estimated grass height with high accuracy and speed using the structure from motion (SfM) and portable light detection and ranging (LiDAR) systems. The shapes of leaf tip surface and ground in grassland were determined by unmanned aerial vehicle (UAV)-SfM, pole camera-SfM, and hand-held LiDAR, before and after grass harvesting. Grass height was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The time it takes for each emitted light beam to be reflected back to the LiDAR sensor receiver is used to develop a point cloud dataset for each target object. Obanawa et al [117] reported an average absolute error of 12 mm (±10 mm) (R 2 = 0.93) at a 20 mm resolution for LiDAR prediction of grass height on Italian ryegrass pasture in Japan. Disadvantages of LiDAR include its relatively high cost and susceptibility to high measurement error in windy conditions [118,119].…”
Section: Remote Sensingmentioning
confidence: 99%
“…The time it takes for each emitted light beam to be reflected back to the LiDAR sensor receiver is used to develop a point cloud dataset for each target object. Obanawa et al [117] reported an average absolute error of 12 mm (±10 mm) (R 2 = 0.93) at a 20 mm resolution for LiDAR prediction of grass height on Italian ryegrass pasture in Japan. Disadvantages of LiDAR include its relatively high cost and susceptibility to high measurement error in windy conditions [118,119].…”
Section: Remote Sensingmentioning
confidence: 99%
“…Photographic determinations of pasture height may be carried out with a simple red-green-blue (RGB) camera mounted onto a UAV or other vehicle [19] or held on a pole [20]. Ground control points (GCPs) are high-visibility objects used to provide a frame of reference for determining the position of the UAV in the pasture being photographed and are georeferenced using GPS after they are placed in the pasture [21].…”
Section: Use Of Proximal Sensors To Measure Plant Height and Predict Biomassmentioning
confidence: 99%
“…Light detection and ranging (LiDAR) generates point clouds much like SfM techniques but relies on a different mechanism to do so. With LiDAR, a laser aimed at the ground bounces back to a sensor, which records the time it took for the light to return, and from this interval calculates the distance from the LiDAR equipment [20].…”
Section: Use Of Proximal Sensors To Measure Plant Height and Predict Biomassmentioning
confidence: 99%
See 2 more Smart Citations